2018
DOI: 10.1017/s1751731117001872
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for fatty acid compositions in the longissimus dorsi muscle of Hanwoo cattle

Abstract: We estimated the heritabilities (h 2) and genetic and phenotypic correlations among individual and groups of fatty acids, as well as their correlations with six important carcass and meat-quality traits in Korean Hanwoo cattle. Meat samples were collected from the longissimus dorsi muscles of 1000 Hanwoo steers that were 30-month-old (progeny of 85 proven Hanwoo bulls) to determine intramuscular fatty acid profiles. Phenotypic data on carcass weight (CWT), eye muscle area (EMA), back fat thickness (BFT), marbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…AS and WS had significantly lower (p<0.05) shear force compared with CS in both LTL and SE muscles, and more than a 1.5-fold decrease was observed in the shear force of AS compared with CS. As tenderness increased with a decrease in shear force ( Bhuiyan et al, 2017 ) AS and WS crossbreeds might produce more tender meat, with AS has a slight edge over WS.…”
Section: Resultsmentioning
confidence: 99%
“…AS and WS had significantly lower (p<0.05) shear force compared with CS in both LTL and SE muscles, and more than a 1.5-fold decrease was observed in the shear force of AS compared with CS. As tenderness increased with a decrease in shear force ( Bhuiyan et al, 2017 ) AS and WS crossbreeds might produce more tender meat, with AS has a slight edge over WS.…”
Section: Resultsmentioning
confidence: 99%
“…After storage for ~24 h at 4°C, samples of longissimus dorsi (LOD) muscle were collected from the junction between the 12th and 13th ribs and were stored at −20°C until further analysis. The intramuscular fatty-acid levels were determined according to Bhuiyan et al (2017). Briefly, total lipids were extracted from 200 mg of intramuscular adipose tissue according to a modification of the method of Folch et al (1957).…”
Section: Animals and Phenotypesmentioning
confidence: 99%
“…Epidemiological studies have shown that circadian misalignment is associated with a range of diseases, such as obesity, NAFLD, and IR [34,35]. Oleic acid (OA) (C18:1) and palmitic acid (PA) (C16:0), two of the most abundant fatty acids in the human diet, could significantly disrupt the circadian rhythm and damage biological clock function [21,22,36]. Consistent with the previous study, we found that the control group maintained a relatively good oscillation rhythm, whereas FFA addition down-regulated the expression of Clock, Bmal1, and Clock-related genes and engendered peak ectopic (Figure 5).…”
Section: Discussionmentioning
confidence: 99%